陳旧性両側顎関節脱臼に両側下顎枝垂直骨切り術を行った１例 - 野上, 晋之介; 柳沢, 佑太; 大竹, 義雄; 山内, 健介; 岩間, 亮介; 佐藤, 舜 (日本口腔外科学会雑誌, 2024)
Chronic bilateral dislocation of the temporomandibular joint is a relatively rare disorder that occurs when TMJ dislocation has not been repaired for a long period of time. It is often treated by surgical repositioning. We report a case of chronic bilateral anterior dislocation of the temporomandibular joint due to six months of neglect, which was treated via a bilateral intraoral vertical ramus osteotomy (IVRO). The patient was a 62-year-old man. He developed TMJ dislocation triggered by excessive opening of the mouth due to yawning. The patient was advised to see an oral surgeon, however he left the condition untreated for six months. Thereafter the patient was diagnosed with chronic temporomandibular joint dislocation and was referred to the Department of Oral and Maxillofacial Surgery, Tohoku University Hospital. The painless opening amount was 40 mm and the mouth could not be closed. Panoramic radiographs showed anterior dislocation of the bilateral temporomandibular joints. We attempted to restore the condyle under general anesthesia, however repositioning of the condyles was difficult, so a bilateral osteotomy (IVRO) was performed on the jaw to close the mouth. Three years after surgery, the oral mobility range was maintained at 36 mm, and no recurrence was observed.